1995
DOI: 10.1093/oxfordjournals.annonc.a059109
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics and pharmacodynamics of irinotecan (CPT-11) and active metabolite SN-38 during phase I trials

Abstract: 168 pharmacokinetic data sets were obtained in 107 patients (97 first courses, 43 second courses, 23 third courses, 4 fourth courses, and 1 fifth course). Rebound concentrations of CPT-11 were frequently observed at about 0.5 to 1 h following the end of the i.v. infusion, which is suggestive of enterohepatic recycling of the drug. Model-independent analysis yielded the following mean population pharmacokinetic parameters for CPT-11: a terminal half-life of 10.8 h, a mean residence time (MRT) of 10.7 h, a volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
73
2
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(94 citation statements)
references
References 19 publications
16
73
2
3
Order By: Relevance
“…The contribution of plasma SN-38 concentrations in CPT-11-related side-effects is well recognized (5,6). In the present study, a significant correlation was obtained between plasma SN-38 concentrations and neutropenia induction (Fig.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The contribution of plasma SN-38 concentrations in CPT-11-related side-effects is well recognized (5,6). In the present study, a significant correlation was obtained between plasma SN-38 concentrations and neutropenia induction (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…However, in clinical practice, the adjustment of the optimal dose of CPT-11 for an individual patient remains unclear, since pharmacokinetic parameters of CPT-11, as well as the incidence of CPT-11-related side effects, are markedly varied among patients (1,3,5,6). The clinical significance of inherited genetic polymorphisms of UGTs involved in SN-38 glucuronidation is well recognized in association with CPT-11-induced side effects (2,(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been suggested that this methodology may be useful for dose escalation designs where many concentrations fall below assay limits (Schoemaker and Cohen, 1996), many population studies to date have focused on sparse data collected during Phase III of drug development or routine clinical practice (Samara and Granneman, 1997). The population approach has been applied in cancer chemotherapy, especially for drugs such as carboplatin (Chatelut et al, 1995), docetaxel (Bruno et al, 1996) and etoposide (Nguyen et al, 1998) and in the analysis of phase I data (Chabot et al, 1995;Launay Iliadis et al, 1995). Limited sampling strategies employing Bayesian approaches have also been used to estimate population parameters during early drug development (Jodrell et al, 1994;Reyno et al, 1995;McLeod et al, 1996;Piscitelli et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we are confident that dosing heterogeneity did not significantly confound our replication results because irinotecan has been shown to demonstrate dose linear pharmacokinetics over a wide range of doses. 38 Regarding our statistical approach, the assessment of replicated associations is not based on hypothesis testing, and therefore using P-values as our main criteria for replication would have been inappropriate. Moreover, given the influence of sample size on P-values, utilization of Pvalues as the main criteria for replication could have resulted in false negative results.…”
Section: Discussionmentioning
confidence: 99%